"Interpretation" in RIBLA: A Multifaceted Meaning - Cardona Ramírez, Hernán (Verbum Vitae, 2024)
This article analyses the evolution and meaning of “Interpretation” in the journal Revista de Interpretación Bíblica Latinoamericana (RIBLA [Latin American Journal of Biblical Interpretation]) from its inception in 1988 up to 2023, with a focus on the period 2012–2023. Launched in Costa Rica in 1988, RIBLA reflects the faith experiences and struggles of Latin American communities and churches from the popular Reading of the Bible in Latin America and the hermeneutics of liberation. In its early days, RIBLA focused on biblical hermeneutics as the interpretation of the text in its historic context in relation to the life of the Ecclesial Base Communities (BECs) of the continent. In the years 1988–2011, it emphasized a liberationist interpretation of the Bible, with a focus on Indigenous communities. The dialogue between Revelation in indigenous religions and Revelation in traditional religions is important, as is the figure of Paul in the theology of liberation. Between 2012 and 2023, RIBLA restates the importance of biblical narratives in collaborative interpretations. In short, “interpretation” in RIBLA is seen as fundamental to confront the challenges of Latin America and the world. With a constant commitment to the Word of God, contextualised liberation and a dialogue between hermeneutics and hermeneutics of liberation, the journal offers an “unfinished” interpretation that is “open” to new considerations, as a beacon of critical reflection in the midst of historic crises.